Addition of Facilities to Bottle Capping Machine - Antoni Yohanes; Firman Ardiansyah Ekoanindiyo; Endro Prihastono (Jurnal Serambi Engineering, 2024)
Little industry participated in CV milk drink items. Memory Susu Nusantara on Jalan Tirto Agung, Semarang city, the method involved with cappingmilk bottle covers is as yet done physically. This exploration will have some expertise in planning bottle shutting apparatuses and tables utilizing anthropometric strategies to make bundling time more successful. Sat around idly causes significant expenses, aside from that it additionally causes laborers bother in bottle shutting procedures. In planning this device, the anthropometric information utilized is Hip Level, Hand Reach, Hip to Shoulder, Shoulder Width information. In light of the information acquired and the consequences of the information computations, it was found that the information got was uniform since it was still inside the upper control cutoff points and lower control limits. All in all, by planning a jug covering device with an extra table, it decreases sit around, laborers will turn out to be more agreeable, on the grounds that there is an extra table to kill the time taken by laborers to gather bottles. This new apparatus will make laborers more proficient in shutting bottles contrasted with physically, subsequently acquiring useful time simultaneously.